Pengaruh Disiplin Kerja dan Worklife Balance Terhadap Produktivitas Karyawan PT. Bank Rakyat Indonesia Kantor Cabang Sukabumi - Jaya, Umban Adi; Herlina, Elin; Wulandari, Dwiwahjuni; Priyana, Indarta; Maulana, M. Afrizal (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study investigates the impact of work discipline and work-life balance on employee productivity at PT Bank Rakyat Indonesia's Sukabumi Branch Office. A quantitative correlation approach was used to obtain data from 100 employees via a Likert questionnaire. The findings of the investigation revealed that both work discipline and work-life balance had a considerable favorable impact on employee productivity. It was discovered that the higher the level of work discipline and work-life balance, the higher the expected work productivity. Although no significant relationship was found between work discipline and work-life balance, both together affect work productivity. Regression analysis shows that both have a significant impact individually on work productivity. Work discipline affects work productivity by 0.261 units, while work-life balance affects it by 0.335 units. Furthermore, the coefficient of determination shows that about 20.5% of the variation in work productivity can be explained by work discipline and work-life balance. Although the regression model can explain a small portion of the variation in work productivity, there are still other factors affecting work productivity that are not included in this model. This study provides important insights for company management in improving employee productivity through the implementation of good work discipline and optimal work-life balance. It is hoped that the results of this study can be the basis for company policy in establishing a favorable workplace and supporting employee productivity.